(untitled) (Transport systems and technologies, 2018)
The article deals with technical and design deficiencies of brake linkage of freight rolling stock. Advantages and disadvantages of different types of pads are given. The installation of composite shoes on cars, the lever transmission of which has a gear ratio for cast-iron pads, can lead to jamming of wheel sets, and also threatens the safety of traffic. Optimizing the brake linkage under the composite pads will not only simplify the design, maintenance and repair, reduce its weight and cost, but also improve traffic safety. The forces acting in the standard design of universal transmission of the platform car for various types of brake pads have been estimated, the most weighty elements of the mechanical transmission have been calculated with the help of the finite element method. It is proposed, using the capabilities of the Femap Siemens PLM Software, to optimize the elements of the brake linkage. An example of topological optimization of brake linkage elements of a freight car is implemented. It is concluded that the modernization of the elements of mechanical transmission under the composite pads will simplify their design, maintenance and repair, reduce their weight and cost, and improve traffic safety.